Design of a meta search system for legal domain - Kanapala A.; Pal S.; Pamula R. (My University, 2025)
With proliferation of social media, legal data on the Web is increasing. Although online forums can only provide rudimentary legal assistance, people increasingly seek help online and often their legal information need gets partially met. Lack of easy natural language search amenity in these forums, nevertheless, deprives a novice user from quickly retrieving answers to similar questions which are previously asked. Also, they do not get a feel whether there are previous legal cases pertaining to the same issue or not. We introduce a meta search system with graphical easy-to-use interface that provides search facility on previously asked questions in the social media as well as on formal court proceedings. We used Terrier system in the back-end which indexes two different document collections (court proceedings and online legal forums). The Google-style search interface allows users to describe her legal information need. The retrieval is performed from the two indexes and best-matched documents are displayed. Navigation through hyperlinks enables the user to instantly access documents from either domain within the same interface in parallel. The objective is to make an automated meta search system that can provide holistic guidance in legal matters to the end user. © 2017 IEEE.